Assessing The Risk Of Knowledge Decline Among Patients With Dengue Virus Infection: A Systematic Review In Saudi Arabia 2024 (The Review of Diabetic Studies, 2024)
BackgroundDengue fever, caused by the dengue virus and transmitted through Aedes mosquitoes, is a growing public health concern, particularly in tropical and subtropical regions. Traditionally associated with febrile and hemorrhagic symptoms, recent research suggests a potential link between dengue and cognitive impairments. Dengue fever cases are on the rise in Saudi Arabia. Studies pertaining to public knowledge of dengue prevention have frequently been used to better understand the publics’ needs towards dengue. Dengue fever (DF) is one of the most prevalent arboviral infections worldwide. In Saudi Arabia, the dengue positive serological cases as well as the presence of the dengue vector Aedeses Egypt have raised health concerns, highlighting the need to enhance the dengue surveillance system.  Regarding dengue fever in a large and high-risk region in Saudi Arabia . This study conducted a systematic review of assessing the risk of Knowledge decline among patients with dengue virus infection,Aim of the systematic review: To assessing the risk of Knowledge decline among patients with dengue virus infection in Saudi Arabia systematic review 2024. Method: This systematic review followed preferred reporting items for systematic reviews guidelines. A comprehensive literature search was conducted in PubMed, EMBASE, and Web of Science up to December, 2024. Studies assessing the risk of Knowledge decline among patients with dengue virus infection in Saudi Arabia. Results: The systematic review databases yielded a total of129 studies. After excluding 823 duplicates, 866 studies were screened based on titles and abstracts. Irrelevant studies were removed, including nonhuman studies, case reports, studies not related to dengue, reviews, short communications, and studies without cognitive outcomes. Six articles were retrieved for full text screening, with 1 further excluded, for not reporting cognitive outcomes. Finally, 7 studies met all the eligibility criteria for Inclusion in the systematic review, covering a total of 2873 participants from Saudi Arabia and other country as shown in Table1.Conclusion: This systematic review suggests that dengue virus infection may affect risk of Knowledge decline in both acute and long-term contexts. However, the current evidence is not strong enough to establish a conclusive link. Further research with larger sample sizes and Longitudinal studies is essential to confirm the impact of dengue virus on risk of Knowledge decline.